Prevalence of hypertension and diabetes and associated risk factors among people living with human immunodeficiency virus in Southern Ethiopia - Badacho, Abebe Sorsa; Mahomed, Ozayr Haroon (Frontiers in Cardiovascular Medicine, 2023)
Background Access to antiretroviral therapy (ART) allows people living with HIV (PLWH) to live longer. Consequently, non communicable diseases (NCD) have emerged as the main drivers of ill health, disability, and premature death. This study assessed the magnitude of hypertension and diabetes and risk factors among PLWH receiving ART in Ethiopia. Methods A cross-sectional study was conducted using an analytical component. Data were collected through face-to-face interviews, physical measurements, and chart reviews of the 520 adults. Associations between the demographic and clinical attributes of hypertension and diabetes were assessed using logistic regression models. Results Prevalence of hypertension was (18.5%) (95% CI: 15.2%–21.7%), and diabetes was (6.9%) (95% CI: 4.8%–9.2%). More than two-thirds (70.8%) and 61% were newly diagnosed with hypertension and diabetes, respectively. Age > = 45 years [adjusted odds ratio (AOR) = 2.47], alcohol consumption (AOR = 4.51), Insufficient physical activity (AOR = 3.7), BMI ≥25 (AOR = 3.95), family history of hypertension (AOR = 7.1), and diabetes (AOR = 4.95) were associated with hypertension. Age ≥45 years [adjusted odds ratio (AOR) = 2.47], BMI ≥25 (AOR = 1.91), Central obesity (AOR = 3.27), detectable viral load (AOR = 4.2), hypertension (AOR = 4.95) and duration of ART >10 years (AOR = 3.12) were associated with diabetes. Conclusions A combination of modifiable and nonmodifiable factors increased the risk of hypertension and diabetes. Primary prevention strategies, regular screening for hypertension and diabetes and integration with HIV care in primary health care are the recommended intervention measures.